Urban development and pollution of groundwater resources (Case study: Hamadan–Bahar Plain) - Mohammad Sadegh Oliaei; Javad Fasihi Ramandi; Mohsen Kakaie; Zoaeddin Almassi (علوم محیطی)
Introduction: Population growth and the increase of water demand in different sectors of agriculture, drinking, industry and health, groundwater resources have faced a lot of pressure. This issue along with severe and prolonged droughts has created the conditions for country particularly for arid and hyper arid areas which has encountered the serious challenges in the field of water quantity and quality. In this study, qualitative changes in the trend of drought and water resources in Hamadan - Bahar plain, as one of the most important Agriculture centers in Iran has been considered.Materials and methods: A number of 23 wells were sampled across the plain, on September 2015. To evaluate the strategic parameter in the study, the standard methods were used. All anions and cations in the water with fluoride, nitrate and nitrite were measured.Results and discussion: The results of the reduction of groundwater level decline by an average of 1 meter per year, respectively. The parameters measured from the adverse changes in the quality of underground water sources had indicated. The maximum measured nitrite and nitrate, respectively, 74.8 and 0.41 mg/L for the area. The collection of samples in about 27% of the samples close to the national standard of 43 milligrams per liter, and the average was alert at the border. However, the average total of 24.2 mg/L for nitrates. The amount of fluorine in most cases was lower than the international standard. In some cases the amount of sulfate that flows through the city sewage was being too standard.Conclusion: Considering the results, it can be concluded that the only basic principal method of preventing dangerous consequences of falling water table levels and reducing the quantity and quality of underground water resources is proper and lawful consumption of water to avoid uncontrolled withdrawal of groundwater.